Ruthenium and iron complexes with benzotriazole and benzimidazole derivatives as simple models for proton-coupled electron transfer systems - Rocha,Reginaldo C. (2001)
Iron and ruthenium complexes of the type [M-LH]n (where M = RuII,III(NH3)5(2+,3+), RuII,III(edta)2-,- [edta = ethylenedinitrilotetraacetate], or FeII,III(CN)5(3-,2-) and LH = benzotriazole or benzimidazole) were prepared and characterized in aqueous solutions by means of electrochemical and spectroelectrochemical methods. Special emphasis was given to the pH-dependent redox processes, exhibited by all the investigated complexes. From their related Pourbaix diagrams, which displayed a typically Nernstian behavior, the pKa and formal reduction potential values were extracted. In addition, these E1/2 versus pH curves were also used to illustrate the partitioning relationship concerning the redox and acid-base species, and their interconversion equilibria. The active area in which the dependence of the M III/M II couple on the pH takes place, as delimited by pKaIII and pKaII, was taken into account in order to evaluate the usefulness of such simple complexes as models for proton-coupled electron transfer (PCET). The results were interpreted in terms of the acceptor/donor electronic character of the ligands and sigma,pi-metal-ligand interactions in both redox states of the metal ion.